Upacara Wuad Wa’i di Manggarai, Flores, dalam Perspektif Evangelisasi - Tamur, Martin (Perspektif, 2014)
Being a migrant people is not a new phenomenon at all in the world of today. People are relatively easy moving from one place to the other, leaving their birthplace for studying, working, and for a betterment of life. Manggarainese of West Flores is one ethnic group of these migrant peoples, leaving their region and province to another islands in Indonesia, such as Bali, Jawa, Sulawesi, Kalimantan, even crossing the border to Malaysia, to become TKIs (Tenaga Kerja Indonesia, Indonesian workers) abroad. The article describes an important rite performed for the would be migrants, either for their further study or for some work. The rite is called Wuad Wa’i, which is basically a kind of ‘mission rite’: thanking God (Mori Kraeng, Mori Jari Agu Dedek/ Pencipta) for his divine providence as well as imploring his guidance for the faithfuls. The main intention of the rite is actually to support the would be migrant: offering him/her some advise for the success in the near future and reminding him/her of their being Christian. It is culturally and spiritually very important, because he/she will be living among people of other faiths, who are mostly the majority. The writer is suggesting that it might be also possible to give the Wuad Wa’i rite the spirit of new evangelization, particularly, in reminding the would be migrant not only to become a successful student or worker but also to be witness of Christian faith to his/her new neighbours, whatever the new environment would be like.